Pengaruh Aerobic Exercise Untuk Meningkatkan Fleksibilitas Hamstring Pada Calon Jamaah Umrah Kbih Al-Ikhlas Jakarta - Agus Tiyawan; Nala Tsaniyah Hendrawan (LPPM Universitas Abdurrab, 2020)
ABSTRACT Background: Umrah worship is usually performed by most Muslims aged 50 years or older. As you age you will experience a decrease in flexibility that can interfere with activities during the Umrah. Objective: This study aims to determine the effect of aerobic exercise to increase hamstring flexibility in prospective Umrah KBIH Al-Ikhlas Jakarta pilgrims. Method: In this study using a randomized one group pre and post test experimental method. This research was conducted at KBIH Al-Ikhlas Jakarta with a total sample of 20 people taken at random according to inclusion and exclusion criteria. The training provided in the form of aerobic exercise with brisk walking and measurement of hamstring flexibility is measured by sit and reach test. Data were processed and analyzed with SPSS 16 software applications. Results: Obtained with SPSS 16 software data that is normally distributed and homogeneous. Hypothesis test results obtained with p = 0,000 means p <0.05 then there is the effect of aerobic exercise to increase the flexibility of hamstring on the pilgrims ummah pilgrims KBIH Al-Ikhlas Jakarta. Conclusion: What can be obtained from this study is that there is an effect of aerobic exercise to increase hamstring flexibility in prospective pilgrims from KBIH Al-Ikhlas Jakarta. Keywords: Aerobic Exercise, Hamstring Flexibility, Elderly Umrah Candidates